Accident prevention in agriculture in the ASL1 Abruzzo Local Health Service: protection facilities for tractors - Pompei, Domenico; Rossi, Roberta; Vecchiola, Rita; Angelone, Anna Maria; Fabiani, Leila (La Medicina del Lavoro, 2015)
Background: The ASL1 workplace prevention and safety service in Abruzzo has been conducting workplace inspections on agricultural and livestock farms in the province of L’Aquila since 2011, mainly in the areas of Avezzano, Sulmona and L’Aquila. The agricultural sector in Abruzzo is characterized by high rates of accidents and the ratio of fatal injuries/total injuries is higher than the industry and services sector. Objectives: To evaluate the presence or absence of safety devices , i.e. compliance or otherwise with regulations for tractors, and of any variable factor that could be associated with the safety of the vehicle. Methods: Between 2011 and 2013, 98 farms in the province of L’Aquila were inspected. The data resulting from the inspections was collected by the use of a checklist. An univariate logistic regression analysis was conducted in which the vehicles that complied with regulations were considered as the dependant variable, and the age of the tractor owner, the acres of worked land and the type of farm were considered as explanatory variables. Statistical elaboration was carried out using the Stata 12 programme. Results: Out of a total of 298 tractors that were checked, 64.8% did not comply with regulations due to absence or unsuitability of one or more safety devices such as: a protective device in case of overturning; retention system of the driver; mounting and dismounting from the vehicle; protection of moving parts and hot parts; PTO (Power Take Off) protection device. A significant association between non-compliance of vehicles and the age of the owner and  acres worked was observed, whereas no statistical significance was observed for the association with the farm type variable. Conclusion: Our study showed that farms where the owner’s age is between 50 and 64 years and where more acres of land are worked are those where the agricultural or forestry tractors had lower levels of compliance with regulations.